Advanced business analytics : using Jamovi and R - Munmun Ghosh (New Delhi Cengage, 2025)
Are you ready to dive deeper into the world of numbers and unlock the secrets they hold? Whether you are a student, researcher, or data analyst, this book is your ultimate guide to mastering advanced statistical and analytical concepts in a simple, jargon-free way. Building on the solid foundation of Business Statistics: Using Excel, SPSS, and R, this book takes you one step higher, offering easy-to-follow, step-by-step instructions for all the complex analyses like Structural Equation Modelling (SEM), Mediation and Moderation analysis, PLS-SEM, and many more. No more relying on others for validation; this book empowers you to handle advanced statistics confidently! With a focus on the open-access software JAMOVI and R, you will learn how to use these powerful tools to perform sophisticated analyses without traditional statistical software's steep learning curve. Whether you are a beginner or an experienced user, this book will guide you through practical business cases, helping you translate data into actionable insights. Ready to conquer the numbers? Get your copy now!
Keywords: Business Analytics